Answer:
(a) t = 5.66 s
(b) t = 8 s
Step-by-step explanation:
(a)
Here we will use 2nd equation of motion for angular motion:
θ = ωi t + (1/2)∝t²
where,
θ = Angular Displacement = (3.7 rev)(2π rad/1 rev) = 23.25 rad
ωi = initial angular speed = 0 rad/s
t = time = ?
∝ = angular acceleration = 1.45 rad/s²
Therefore,
23.25 rad = (0 rad/s)(t) + (1/2)(1.45 rad/s²)t²
t² = (23.25 rad)(2)/(1.45 rad/s²)
t = √(32.06 s²)
t = 5.66 s
(b)For next 3.7 rev
θ = ωi t + (1/2)∝t²
where,
θ = Angular Displacement = (3.7 rev + 3.7 rev)(2π rad/1 rev) = 46.5 rad
ωi = initial angular speed = 0 rad/s
t = time = ?
∝ = angular acceleration = 1.45 rad/s²
Therefore,
46.5 rad = (0 rad/s)(t) + (1/2)(1.45 rad/s²)t²
t² = (46.5 rad)(2)/(1.45 rad/s²)
t = √(64.13 s²)
t = 8 s